2011
DOI: 10.5657/fas.2011.0226
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Proficiency Test Specimen for Enumerating Escherichia coli in Molluscan Bivalve Shellfish

Abstract: This study was conducted to develop a proficiency test (PT) specimen for the enumeration of Escherichia coli, a sanitary indicative bacterium, in molluscan bivalve shellfish. The common mussel Mytilus edulis was chosen as a matrix for the PT specimen. Mussels were artificially bioaccumulated for approximately 3 h with E. coli culture. After determining the homogeneity of samples, samples were distributed to 17 participants involved in the proficiency testing program. The enumeration of E. coli was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Thus, V. vulnificus is successfully bioaccumulated inside the oyster, and the cell population tends to be maintained thereafter. These results were consistent with the previous reports that bacterial cells were accumulated in shellfish by the bioaccumulation process (Correa et al, 2007 ; Kwon et al, 2011 ). Dore et al ( 1995 ) also reported that the initial bacterial population rapidly increased and was continuously maintained without employing the relaying or depuration process.…”
Section: Resultssupporting
confidence: 94%
“…Thus, V. vulnificus is successfully bioaccumulated inside the oyster, and the cell population tends to be maintained thereafter. These results were consistent with the previous reports that bacterial cells were accumulated in shellfish by the bioaccumulation process (Correa et al, 2007 ; Kwon et al, 2011 ). Dore et al ( 1995 ) also reported that the initial bacterial population rapidly increased and was continuously maintained without employing the relaying or depuration process.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, to check the e ciency of the depuration, several studies showed the arti cial bioaccumulation of the shell sh with the microbial pathogen followed by its enumeration of the cells during the process of depuration (Croci et al, 2002;Marino et al, 2005;Schneider et al, 2009). Martins et al (2006) and Kwon et al (2011) reported a clam Thylacodes decussatus and a mussel Mytilus edulis bioaccumulated by Escherichia coli. In this study, we selected paci c oysters for the bioaccumulation of V. cholerae and V. vulni cus, respectively (detail procedure described in Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to check the e ciency of the depuration, several studies showed the arti cial bioaccumulation of the shell sh with the microbial pathogen followed by its enumeration of the cells during the process of depuration (Croci et al, 2002;Marino et al, 2005;Schneider et al, 2009). Martins et al (2006) and Kwon et al (2011) reported a clam Thylacodes decussatus and a mussel Mytilus edulis bioaccumulated by Escherichia coli. In this study, we selected paci c oysters for the bioaccumulation of V. cholerae and V. vulni cus, respectively (detail procedure described in Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%